Peningkatan Nilai Tambah Produk melalui Pengolahan Bakso Ikan Skala Rumah Tangga bagi Pembudidaya Gurami Kabupaten Tulungagung - Lisanty, Nina; Pamujiati, Agustia Dwi; Probojati, Rasyadan Taufiq (Journal of Dedicators Community, 2022)
The Covid-19 pandemic has harmed freshwater fish cultivators, mainly gourami. Cultivators complained and were threatened with bankruptcy because not only have the selling price been low since the start of the pandemic, but the price of feed has also continued to rise. The situation encouraged gourami cultivators to switch to other types of cultured fish, like catfish and ornamental fish such as koi. The Community Service Team initiated to offer a solution in increasing the added value of gourami through processing it into nutritious fishball. The main result of this activity was to increase the added value of the product to increase selling value, product quality, industrial productivity, employment, income, and the welfare of gourami cultivators and their families. The activity was carried out by applying a participatory approach model and training in processing and producing gourami fishball for several groups of cultivators in several villages in Kalidawir District, Tulungagung. After the training was conducted and the fishball product was created, an organoleptic test was carried out to determine public acceptance of the product.